TEACHING WRITING NARRATIVE TEXT THROUGH PICTURE SERIES TO THE TENTH GRADE STUDENTS AT SMA NEGERI 5 LUBUKLINGGAU - Dewantara, Jaka; syaprizal; Triyogo, Agus (Lingustic, Literature and English Education, 2021)
The problem in this study was Teaching Writing Narrative Text through Picture Series were able to improve students skill at X grade of SMA N 5 Lubuklingau in academic year 2017/2018?”. The method of study was pre – experimental method. The population of this study was all of the tenth grade students of SMA Negeri 5 Lubuklinggau in academic year 2017/2018. The sample was taken through cluster random sampling consisting of 33 students of X.1 class the data were collected through written test. In analyzing the data, writer used four techniques, individual score, conversion of individual score, normality and paired t-test. Based on the result of the data analysis, there was improvement of the average scores or the average ability from the pre-test (40.79) to the post-test (66.42). in the pre-test, there were 2 students (6.06%) who were categorized passed, and in the post-test which was given after teaching writing trough picture series there were 18 students (54.54%) who were categorized passed. The result of the matched t-test calculation found out that was 7.32 and the with significance level 5% was 1.697. in this case, was higher than (7.32>1.697). it could be concluded that it was effective to teach writing through picture series to the tenth grade students of SMA Negeri 5 Lubuklinggau in the academic year of 2017/2018.